Bidirectional association between physical activity and depression: the “Como Vai?” cohort study - Bárbara Sutil da Silva; Debora Tornquist; Andrea Wendt; Andréa Dâmaso Bertoldi; Elaine Tomasi; Maria Cristina Gonzalez; Renata Moraes Bielemann; Inácio Crochemore-Silva (Revista Brasileira de Atividade Física e Saúde)
To evaluate bidirectional and longitudinal association between physical activity (PA) and depressive symptoms (DS). This is a cohort study called “Como Vai?” (How are you?), conducted by older population representative sample of the city of Pelotas-Rio Grande do Sul. The analyses used data from the first interview (2014) and follow-up (2019/20). The long version of the International Physical Activity Questionnaire (IPAQ) was applied to assess PA in the leisure, commuting and total domains. The presence of DS was measured using the Geriatric Depression Scale (GDS-10). Linear regression models were used to evaluate bidirectional associations between PA and DS. Analytical sample included 515 individuals with a mean age of 70.7 (± 9.2) years. Each weekly minute of total PA (β: -0.0006; 95% CI: -0.0011; -0.0001) and commuting PA (β: -0.0008; 95% CI: -0.0016; -0.0001) in 2014 predicts worse DS scores in 2019/20. At the same time, DS score in 2014 (β: -9.79; 95% CI: -18.81; -0.76) was a negative predictor of leisure-time PA in the 2019/20 follow-up adjusted for sociodemographic and other health behaviors. However, when adjusted for the respective outcomes at baseline, the associations found were not statistically significant. The present study did not find evidence of bidirectionality between PA and DS and the prospective associations lost statistical significance after adjustment for the respective outcomes at baseline. Other investigations are necessary including more periods of follow-up, objective analyses of PA to complement analyses by domains and, therefore, provide a better understanding of this complex relationship.